2004
DOI: 10.1158/1078-0432.ccr-03-0093
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor (IGF)-I and IGF-II Serum Concentrations in Patients with Benign and Malignant Breast Lesions

Abstract: Purpose: Insulin-like growth factors (IGFs) are potent mitogens for breast cancer cells in vitro, and elevated IGF-I serum levels are a risk factor for breast malignancies. This study evaluated IGF-I and IGF-II serum levels in healthy women and in patients with benign and malignant breast lesions and correlated them with tumor size.Experimental Design: Serum levels of the total and unbound fractions of IGF-I and IGF-II were analyzed in 65 patients with benign and malignant breast lesions and in 38 women withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…Several growth factors such as IGFs (31)(32)(33), epidermal growth factor (34,35), and transforming growth factor h (36) have been reported to modulate breast and lung carcinoma cell proliferation. Among them, however, IGF-I and IGF-II are considered to be the most potent mitogens for carcinoma cells (31,37,38). In the present study, we have provided in vitro and in vivo data that the IGF-I-induced proliferation of MDA-MB231 cells is significantly inhibited by treatment with KB-R7785, neutralizing anti-ADAM28 antibody, or transfection with ADAM28 siRNA, and that injection of ADAM28 siRNA to the MDA-MB231 cell xenografts significantly suppresses tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Several growth factors such as IGFs (31)(32)(33), epidermal growth factor (34,35), and transforming growth factor h (36) have been reported to modulate breast and lung carcinoma cell proliferation. Among them, however, IGF-I and IGF-II are considered to be the most potent mitogens for carcinoma cells (31,37,38). In the present study, we have provided in vitro and in vivo data that the IGF-I-induced proliferation of MDA-MB231 cells is significantly inhibited by treatment with KB-R7785, neutralizing anti-ADAM28 antibody, or transfection with ADAM28 siRNA, and that injection of ADAM28 siRNA to the MDA-MB231 cell xenografts significantly suppresses tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…This was not observed, possibly due to the small tumour size and range of sizes in the present study. One study found a correlation between circulating free IGF2 and breast tumour size, but surprisingly cancer patients showed lower levels of free IGF2 than matched controls, and noteworthy, these findings only became evident after correcting for the changes in body fluid composition in the post-operative state (10).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo evidence includes several large prospective studies and in general they suggest a modestly increased breast cancer risk in individuals with serum total IGF1 levels within the upper normal range (5,6). Some studies have investigated the molar ratio of IGF1 to IGFBP3 (a putative marker of free IGF1) in breast cancer (7), whereas only a few studies include direct analysis of free IGF1 (6,(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of IGFs in adults predominantly occurs in the liver but may also be accomplished by other tissues, since liver-specific disruption of the IGF-I gene has been demonstrated not to affect growth development and maturation in mice (Liu et al 1993, Yakar et al 1999. Several studies have investigated the systemic and tumoral expression of IGF family members in sporadic breast cancer patients and found elevated IGF levels in patients with breast cancer (Peyrat et al 1993, Rocha et al 1997, and a positive correlation with breast tumor size (Singer et al 2004). However, data on the tumoral expression of members of the IGF axis in patients with inherited breast tumors are sparse, and have not been demonstrated to influence systemic IGF-I levels.…”
Section: Introductionmentioning
confidence: 99%